Epidemiological Survey of Peste des Petits Ruminants in Ethiopia: Cattle as Potential Sentinel for Surveillance - Agga, Getahun E.; Raboisson, Didier; Walch, Ludovic; Alemayehu, Fitsum; Semu, Dawit T.; Bahiru, Getahun; Woube, Yilkal A.; Belihu, Kelay; Tekola, Berhe G.; Bekana, Merga; Roger, François L.; Waret-Szkuta, Agnès (Frontiers in Veterinary Science, 2019)
Peste des petits ruminants (PPR) is a highly contagious viral disease of small ruminants; it emerged in countries previously free of the disease following the eradication of rinderpest. PPR is classified by international organizations as the next priority animal disease for global eradication campaign. Assessment of the local situations is the first step in the eradication efforts. The objective of this study was to investigate and compare the seroprevalence of PPR in cattle, sheep and goats under two livestock production systems in Ethiopia: North Shewa zone of Amhara region represents a highland sedentary life style characterized by mixed livestock-crop production system; Zone Three of Afar region represents a lowland nomadic life style characterized by pastoral livestock production system and. A N-competitive ELISA PPR test was performed on sera from 2993 animals ≥ 6 months old sampled at watering and grazing points. Multivariable logistic regression models comparing the seropositivity between the two production systems were built by classifying doubtful results as positive, negative or excluding them from the data. The odds ratio (OR) comparing overall PPR seroprevalence in the sedentary North Shewa Zone compared to the nomadic Zone Three ranged from 19 to 27 (P< 0.001), depending on how doubtful results were classified, which contrasts with what has been reported in the literature. This is not likely to be related solely to vaccination, since seroprevalences in cattle and small ruminants were similarly high or low in the respective zones (0-4% for Zone Three and 20-40% for North Shewa Zone), and cattle were not likely to be vaccinated. The OR of seropositivity for goats compared to cattle ranged from 1.9 (95% confidence interval [CI]: 1.3-2.7; P<0.001) to 2.2 (95% CI: 1.5-3.1; P<0.001) when doubtful results were excluded or classified as negative, respectively. When doubtful results were classified as positive, association between seropositivity and animal species was not significant (P>0.05). Our results suggest to further investigate cattle as sentinel animals for PPR surveillance.